Analysis of Profit Projected Value Due to the Effect of Price Escalations on Construction Projects: Case Study of Ameroro Dam Project, Southeast Sulawesi - Andika, Wahyu; Wibowo, Kartono; Antonius, Antonius (Jurnal Planologi, 2025)
ABSTRACT  Indonesian contractors are facing pressure due to the domino effect of the Russia-Ukraine war. Which triggered a spike in commodity prices, including construction materials. High inflation and rising fuel prices apparently also had an impact on PT Wijaya Karya (Persero) Tbk (WIKA). The BUMN works asked the owners to adjust the contract price. The government has given the green light regarding proposals for price adjustments or contract escalations for infrastructure projects running in the 2022 fiscal year. Based on the above background. This research is an in-depth study to dissect further the analysis of profit projections due to the influence of escalation carried out by the review of the Ameroro Dam Project, Southeast Sulawesi. The research strategy used is literature study and data analysis of the Cost Budget Plan (RAB) for the Ameroro Dam project in Southeast Sulawesi including: Bill of Quantity Data, (ii) Work Unit Price Analysis (AHSP) Data, (iii) Material Price List and (iv) Work Wage Price List. Then a projection of the adjustment value is carried out with projection i using the BPS price index value and projection ii using the Pertamina economic price index. The results from adjustments to projection I amounted to IDR 15,548,548,165 and projection II amounted to IDR 44,854,254,042. From the results of these adjustments, we obtained an increase in the projected contract value i of 2% from the contract value to IDR 1,016,698,604,665 and an increase in the projected contract value i of 4% from the contract value to IDR 1,046,004,310,542. Based on the projection data, there are differences in the adjusted price values. From this data it can be concluded that the index data used is closer to using Pertamina's economic index data.        Keywords: Escalation, Job Unit Price Analysis, Fuel Industry, Reinforced Steel